1993
DOI: 10.1111/j.1471-4159.1993.tb07482.x
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum A Like Type B and Tetanus Toxins Fulfils Criteria for Being a Zinc‐Dependent Protease

Abstract: Although botulinum neurotoxin (BoNT) types A and B and tetanus toxin (TeTx) are specific inhibitors of transmitter release whose light chains contain a zinc-binding motif characteristic of metalloendoproteases, only the latter two proteolyse synaptobrevin. Chelation of zinc or its readdition at high concentration hindered blockade of neuromuscular transmission by BoNT/A and B, indicating that type A also acts via a zinc-dependent mechanism. Such treatments prevented proteolysis of synaptobrevin II in rat brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 6 publications
0
31
0
1
Order By: Relevance
“…Moreover, the H C moiety of diphtheria toxin can be replaced with the binding domain from tetanus toxin without disruption of the acidification-dependent translocation of its enzymatic chain into cells (38). In contrast, the LC-H N moieties with an intact disulfide bridge are crucial for productive translocation (12,39,40). Noncovalent interactions are also involved in maintaining LC-H N interactions that appear to be important for structural stability, as a chimera consisting of the LC of BoNT/A linked to the HC of BoNT/E was poorly expressed, relatively insoluble, and susceptible to proteolysis (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the H C moiety of diphtheria toxin can be replaced with the binding domain from tetanus toxin without disruption of the acidification-dependent translocation of its enzymatic chain into cells (38). In contrast, the LC-H N moieties with an intact disulfide bridge are crucial for productive translocation (12,39,40). Noncovalent interactions are also involved in maintaining LC-H N interactions that appear to be important for structural stability, as a chimera consisting of the LC of BoNT/A linked to the HC of BoNT/E was poorly expressed, relatively insoluble, and susceptible to proteolysis (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…After equilibration, TeTx, a recombinant sample (or buffer as a control) was added and toxin-induced neuromuscular paralysis was determined as the time taken for nerve-evoked muscle contraction to decrease to 10% of original value, as described previously (9,27). For competition studies, conditions designed to minimize toxin uptake into the nerve endings were used.…”
Section: Methodsmentioning
confidence: 99%
“…BOTOX offers the advantages of having a much longer action and greater potency in blocking the release of transmitters and inflammatory/pain mediators via cleavage of SNAP-25, a 206-residue SNARE protein essential for neuroexocytosis (de Paiva et al, 1993). However, additional investigations are required to find a molecular basis for its beneficial effects in some migraineurs (Silberstein et al, 2000;Mauskop, 2002), which are not consistently observed (for review, see Naumann et al, 2008).…”
Section: Introductionmentioning
confidence: 99%